Antinociceptive effect of an ethanolic extract of the aerial parts of Hilleria latifolia (Lam.) H. Walt. (Phytolaccaceae) - Eric Woode; Wonder K.M. Abotsi (Wolters Kluwer Medknow Publications, 2011)
Background : Hilleria latifolia (Lam.) H. Walt. (Phytolaccaceae) is a perennial herb used in Ghanaian traditional medicine for the treatment of various painful conditions. Little scientific evidence exists in literature on the effect of this plant on pain. Materials and Methods : The present study examined the antinociceptive effect of the ethanolic extract of the aerial parts of H. latifolia in chemical (acetic acid-induced abdominal writhing, glutamate, formalin, and capsaicin tests) and thermal (tail immersion test) behavioral pain models in rodents. The possible mechanisms of the antinociceptive action were also assessed with various antagonists in the formalin test. Results : The H. latifolia extract (HLE) together with morphine and diclofenac (positive controls), showed significant antinociceptive activity in all the models used. The antinociceptive effect exhibited by HLE in the formalin test was partly or wholly reversed by the systemic administration of naloxone, theophylline, and atropine. Glibenclamide, ondansetron, yohimbine, nifedipine, and NG -l-nitro-arginine methyl ester (l-NAME), however, did not significantly block the antinociceptive effect of the extract. HLE, unlike morphine, did not induce tolerance to its antinociceptive effect in the formalin test after chronic administration; morphine tolerance did not also cross-generalize to HLE. Interestingly, also, the chronic concomitant administration of HLE and morphine significantly suppressed the development of morphine tolerance. Conclusion : Together, these results indicate that HLE produces dose-related antinociception in several models of chemical and thermal pain, without tolerance induction, through mechanisms that involve an interaction with adenosinergic, muscarinic cholinergic, and opioid pathways.